Before and beyond the micellization of n-alkyl glycosides. A water-1H NMR relaxation study - Cardoso, Marcus V C (Langmuir : the ACS journal of surfaces and colloids, 2013)
The interactions between the headgroups of n-alkyl glycoside (AG) and water molecules were studied by nuclear magnetic transverse relaxation times (T2) of the water protons before and beyond the micellization. Despite the low concentration of the surfactants (mM), their micellization induce strong effect on the T2 values of bulk water when the AG molecules self-aggregate into micelles. This is associated with the decreasing of the fraction of OH headgroups of AG to exchange protons with water molecules due to the OH headgroups intermolecular interactions of AG at the micelle surface. These findings support the computational results described in the literature, which indicate that the water hydrogen bonding to OH headgroups is perturbed at AG micelle surfaces